Myxoma of parotid gland: report of a rare case - Bharadwaj, Barasha S.; Suhana, Asreen; Sharma, Jagannath D.; Deka, Muktanjalee; Beso, Adahra P.; Kalita, Upasana; Goswami, Bibhash C. (International Journal of Research in Medical Sciences, 2023)
Myxomas of head and neck and especially parotid gland are rare. These insidious soft tissue tumours have obscured pathogenesis, can occur at any age, mostly located in the cheek, palate or floor of mouth. They often present with non- specific symptoms like painless slow growing localised swelling in the cheek or around the jaw. Complete excision remains the mainstay of treatment with rare recurrence, no distant metastases and excellent prognosis. Here we reported a case of right sided parotid gland myxoma in a 37 years old man. There were no specific clinical, laboratory or radiological features. Fine needle aspiration cytology was reported as adenoid cystic carcinoma of right parotid gland. Histopathological examination of the specimen confirmed the diagnosis of myxoma. Immunohistochemistry can be helpful, but not necessary to come to a diagnosis.